Cross-Cultural Administration of an Odor Discrimination Test - Sorokowska, Agnieszka (Springer US, 2014)
Olfactory sensitivity can be evaluated by various tests, with “Sniffin’ Sticks” test (SST) being one of the most popular. SST consists of tests for odor threshold, discrimination, and identification. It seems relatively straightforward to administer threshold tests in different groups and societies and it has been shown that odor identification tests requires special adaptation before they can be administered to various populations. However, few studies have investigated the application of an odor discrimination task in various regions/cultures. In the present study, we compared the discrimination scores of 169 Polish people with the scores of 99 Tsimane’, Bolivian Amerindians. The Tsimane’ participants scored very low in the discrimination task, despite their general high olfactory sensitivity. This result suggests that when a discrimination task is chosen as the form of olfactory testing, some additional variables need to be controlled. We suggest three sources of low scores of our participants—their cognitive profile, the cultural background, i.e., little knowledge of the odors used in the discrimination test and problems associated with testing environment.